Environmental Information Disclosure Assessment: The Case of Manufacturing Firms Listed on the Indonesia Stock Exchange - Handoyo, Sofik (The Asian Journal of Technology Management (AJTM), 2021)
This study aimed to assess the environmental information disclosure of listed manufacturing firms on the Indonesia Stock Exchange. Furthermore, this study used the content analysis procedure of the firm’s annual reports and sustainability reporting. The Global Reporting Initiative (GRI) standard was adopted as the guidelines for assessing environmental disclosure. Meanwhile, the evaluated topics are material, energy, water, biodiversity, emissions, effluents and waste, environmental compliance, and supplier environmental assessment. The results showed that manufacturing firms had disclosed environmental information at a moderate level, and the average performance level was relatively low. Furthermore, by topic, the environmental performance levels showed that disclosure related to effluents and waste was the highest, followed by energy, materials, emissions, water, biodiversity, and compliance, respectively. The results indicated that the Indonesian government needs to improve environmental law enforcement for industrial practice. Furthermore, Indonesia’s capital market authority is expected to introduce a sustainability index as part of a business organisation’s concern for environmental protection. The Institute of Indonesia Chartered Accountant (IAI) also needs to consider developing a standard for environmental reporting as an integral part of corporate financial reporting.